Comparative Transcriptome Analysis of Primary Roots of Brassica napus Seedlings with Extremely Different Primary Root Lengths Using RNA Sequencing - Dun, Xiaoling; Tao, Zhangsheng; Wang, Jie; Wang, Xinfa; Liu, Guihua; Wang, Hanzhong (Frontiers in Plant Science, 2016)
Primary root (PR) development is a crucial developmental process that is essential for plant survival. The elucidation of the PR transcriptome provides insight into the genetic mechanism controlling PR development in crops. In this study, we performed a comparative transcriptome analysis to investigate the genome-wide gene expression profiles of the seedling PRs of four Brassica napus genotypes that were divided into two groups, short group (D43 and D61) and long group (D69 and D72), according to their extremely different primary root lengths (PRLs). The results generated 55,341,366–64,631,336 clean reads aligned to 62,562 genes (61.9% of the current annotated genes) in the B. napus genome. We provide evidence that at least 44,986 genes are actively expressed in the B. napus PR. The majority of the genes that were expressed during seedling PR development were associated with metabolism, cellular processes, response to stimulus, biological regulation and signaling. Using a pairwise comparison approach, 509 differentially expressed genes (DEGs) (absolute value of log2 fold-change ≥1 and p ≤0.05) between the long and short groups were revealed, including phytohormone-related genes, protein kinases and phosphatases, oxygenase, cytochrome P450 proteins, etc. Combining GO functional category, KEGG and MapMan pathway analyses indicated that the DEGs involved in cell wall metabolism, carbohydrate metabolism, lipid metabolism, secondary metabolism, protein modification and degradation, hormone pathways and signaling pathways were the main causes of the observed PRL differences. We also identified 16 differentially expressed transcription factors (TFs) involved in PR development. Taken together, these transcriptomic datasets may serve as a foundation for the identification of candidate genes and may provide valuable information for understanding the molecular and cellular events related to PR development.